Epidemiologic Feature of Thyroid Cancer Based on Cancer Registry Data System - B Larijani; M Shirzad; MA Mohagheghi; V Haghpanah; AR Moosavi Jarahi; SM Tavangar; AR Vassigh; A Hossein-nezhad; F Bandarian; R Baradar- Jalili (Tehran University of Medical Sciences, 2005)
This study was undertaken to define the epidemiological aspects of thyroid carcinoma in Iran, an area of endemic iodine deficiency nearly until recently. The Tehran Cancer Institute Data System Registry (TCIDSR) was used to identify patients with different histological types of thyroid cancer (TC) in Iran. Data were analyzed from 438 thyroid cancer cases identified by the TCIDSR in 1998-99. Disease prevalence was calculated by age, time and place. The TCIDSR recorded 438 primary malignancies of the thyroid gland: papillary, follicular, medullary, and anaplastic carcinomas accounted for 67.1%, 10.7%, 5.3% and 4.3% of cases, respectively. The remaining 12.6% was classified as OD (other diagnoses). The prevalence of TC was the highest in Farsis population. The age range of patients was 8-85 yr. Mean patient age was 44.52± 17.03 yr (mean± SD) overall, 47.74± 18.10 yr in male patients and 43.04± 16.34 in female patients. Anaplastic (6.5% vs. 3.3%) and medullary (10.0% vs. 3.0%) cancers were more common in men than women. Against expectation for an iodine-deficient area, the frequency distribution of tumours in our study was closer to that seen in iodine-rich areas. Additional research on the risk factors for thyroid cancer-genetic, ethnic, geographic and environmental is needed to explain the high incidence of PTC overall, and among Farsis population in particular, in Iran.